PERWUJUDAN GOOD GOVERNANCE MELALUI FORMAT REFORMASI BIROKRASI PUBLIK DALAM PERSPEKTIF HUKUM ADMINISTRASI NEGARA - Sudrajat, Tedi (Jurnal Dinamika Hukum, 2009)
Law Administration is being developing in atmosphere that governmental start to arrange the society in law aspect. It is impact with governmental orientation that to create development in society. Then generate implication in the form of usage a set component, element, or element of subsystem with all his attribute, where which one another and each other interconnected, and interdependent so that in its entirety is a[n integrated unity or a[n totality, and also have specific-purpose or role among the law system and state administrate system. In this article will be explained about a set component, element, or element of subsystem to influence Law Administration State by good governance in materialization of public bureaucracy reform in Indonesia. Kata Kunci   :  Hukum Administrasi Negara, good governance dan reformasi birokrasi publik